Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2019
DOI: 10.3390/metabo9120293
|View full text |Cite
|
Sign up to set email alerts
|

Degradation of Extracellular NAD+ Intermediates in Cultures of Human HEK293 Cells

Abstract: Nicotinamide adenine dinucleotide (NAD) is an essential redox carrier, whereas its degradation is a key element of important signaling pathways. Human cells replenish their NAD contents through NAD biosynthesis from extracellular precursors. These precursors encompass bases nicotinamide (Nam) and nicotinic acid and their corresponding nucleosides nicotinamide riboside (NR) and nicotinic acid riboside (NAR), now collectively referred to as vitamin B3. In addition, extracellular NAD+ and nicotinamide mononucleot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
27
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 34 publications
(30 citation statements)
references
References 42 publications
2
27
0
Order By: Relevance
“…Nam is released from the cells into the culture medium. These results are in line and extend our previous observations using different experimental conditions [40].…”
Section: Ent Inhibition Suppresses Nr Utilization By Hek293 Cells Forsupporting
confidence: 94%
See 1 more Smart Citation
“…Nam is released from the cells into the culture medium. These results are in line and extend our previous observations using different experimental conditions [40].…”
Section: Ent Inhibition Suppresses Nr Utilization By Hek293 Cells Forsupporting
confidence: 94%
“…As shown in this study and a previous study [40], once NR enters the cell, it is actively metabolized to form Nam. The observed formation of Nam can be explained by the fact that NR is metabolized into NAD + , which is then converted to Nam by NAD + -consuming enzymes.…”
Section: Discussionsupporting
confidence: 78%
“…A far more physiologically relevant supplementation dose is 100 μM, which still showed 15 ± 2.1% cytotoxicity. We selected the 100 μM concentration for further study due to its physiological relevance and published work with NR and NRH, showing the efficient restoration of the intracellular NAD pools and cells' metabolic activity with that concentration [ 37 ]. At 100 μM, NRH is reported to increase neuronal NAD + levels by approximately 5-fold over control [ 32 ]; however, in the present study, NRH is exposed to HepG3 at this concentration resulted in 15 ± 2.1% cytotoxicity ( Fig 2B ).…”
Section: Resultsmentioning
confidence: 99%
“…However, how these metabolites, as well as those exogenously administered, are able to maintain or even increase intracellular NAD levels is still a matter of investigation. A recent work has clearly established that studies on pyridine supplementation and uptake preformed on cultured cells can be severely affected by the culture conditions, since the serum used in the culture medium, even in a heat-inactivated form, contains enzymes responsible of an efficient degradation of NAD and its intermediates [ 27 ]. Taken into consideration the presence of such activities will allow to get a clearer picture of eNAD metabolism.…”
Section: Discussionmentioning
confidence: 99%
“…Alternatively, in the extracellular space NR can be converted to Nam by the activity of CD157 [25]. Some studies have shown that NMN needs to be processed to NR prior to enter the cell [23,[26][27][28], whereas other studies support the direct uptake of the mononucleotide [29,30]. The complexity in the detection and quantification of NR and NMN is the major reason why the mechanism of NMN transport into the cell is still under debate [28,31], and why we still lack a clear picture of NR and NMN availability in the extracellular space.…”
Section: Extracellular Pyridine Metabolitesmentioning
confidence: 99%